2013
DOI: 10.1007/s10517-013-2322-y
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Breast Tumor during Experimental Hyperthyroidism

Abstract: The incidence of breast tumor in inbred C3H-A mice (virgin female) from hyperthyroid, hypothyroid, and euthyroid control groups at week 44 of the experiment was 86.67, 30, and 62.5%, respectively. The percentage of metastatic lymph nodes in these groups was 65.9±16.7, 35.9±5.9, and 53.9±7.2%, respectively (p<0.005). It was shown that hyperthyroidism was associated with increased incidence and aggressiveness of breast tumor, while hypothyroidism was associated with lower incidence of breast tumor in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Thyroid hormone activity is related to breast cancer. Hypothyroidism is associated with low incidence of breast cancer, and conversely, hyperthyroidism with high incidence and aggressiveness of breast cancer [99]. Statistical studies suggest that high T 3 levels in women are associated with increased overall risk and occurrence of breast cancer.…”
Section: Functional Significance Of Thyroid Hormone and Receptors mentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormone activity is related to breast cancer. Hypothyroidism is associated with low incidence of breast cancer, and conversely, hyperthyroidism with high incidence and aggressiveness of breast cancer [99]. Statistical studies suggest that high T 3 levels in women are associated with increased overall risk and occurrence of breast cancer.…”
Section: Functional Significance Of Thyroid Hormone and Receptors mentioning
confidence: 99%
“…In human breast cell lines MCF-7 and T47D, both T 4 and T 3 promote cell proliferation in a dose-dependent manner [104,105,106]. Hyperthyroidism and hypothyroidism are correlated with the incidence of tumor induction and reduction and aggressiveness of breast cancer in female mice [99]. Interestingly, other reports support anticancer activity of THs, for instance, via downregulation of SMP30 expression and induction of apoptosis in MCF-7 cells through T 3 [76].…”
Section: Functional Significance Of Thyroid Hormone and Receptors mentioning
confidence: 99%
“…Increased risk for breast cancer, especially in women with multiple hospitalizations, was also shown in a large Swedish cohort of GD patients 35 . Specific receptivity of breast cells to thyroid hormones and/or thyroid Abs stimuli may play a role in oncogenesis, as suggested from the high incidence and aggressiveness of breast cancer observed in hyperthyroidism 38 …”
Section: Discussionmentioning
confidence: 82%
“…35 Specific receptivity of breast cells to thyroid hormones and/or thyroid Abs stimuli may play a role in oncogenesis, as suggested from the high incidence and aggressiveness of breast cancer observed in hyperthyroidism. 38 It is not excluded that the association between GD and breast cancer can be partially related to shared predisposing factors, as for instance smoking is a well-described risk factor for both entities. 39,40 Epidemiological studies have not highlighted a significant correlation between GD or GO and increased risk of urinary tract cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A potential link between thyroid conditions and breast cancer has been discussed for decades [10][11][12] . It has been shown that hyperthyroidism is related to an increased incidence and aggressiveness of breast cancer whereas hypothyroidism (HypoT) is associated with a lower incidence of the disease 13,14 . In our laboratory, we have reported that animal growth, breast morphology and body fat mass were modi ed by HypoT 15 .…”
Section: Introductionmentioning
confidence: 99%